2021
DOI: 10.2991/jegh.k.210109.001
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Knowledge, Perceptions and Perceived Risk Concerning COVID-19 in Pakistan

Abstract: The COVID-19 pandemic is one of unmatched scale and severity. A continued state of crisis has been met with poor public adherence to preventive measures and difficulty implementing public health policy. This study aims to identify and evaluate the factors underlying such a response. Thus, it assesses the knowledge, perceived risk, and trust in the sources of information in relation to the novel coronavirus disease at the outset of the COVID-19 pandemic. An online questionnaire was completed between March 20 an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 34 publications
(45 reference statements)
1
4
0
Order By: Relevance
“…The consumption behaviors decreased due to the restriction of objective conditions, but the purchase intention of wild freshwater fish remained at a high level. In addition, Model 1 proved that there was a significant positive relationship between S1 (I am concerned about COVID‐19) and Risk (I think wild freshwater fish are unsafe); that is, the more consumers give importance to the COVID‐19 pandemic, the greater the perceived risk of wild freshwater fish, which is in line with previous research (Haque et al, 2021 ). Thus, H2 was partially confirmed.…”
Section: Resultssupporting
confidence: 87%
“…The consumption behaviors decreased due to the restriction of objective conditions, but the purchase intention of wild freshwater fish remained at a high level. In addition, Model 1 proved that there was a significant positive relationship between S1 (I am concerned about COVID‐19) and Risk (I think wild freshwater fish are unsafe); that is, the more consumers give importance to the COVID‐19 pandemic, the greater the perceived risk of wild freshwater fish, which is in line with previous research (Haque et al, 2021 ). Thus, H2 was partially confirmed.…”
Section: Resultssupporting
confidence: 87%
“…One of our central findings is that among all constructs of the HBM, Pakistani people in Depalpur are moved by the perceived benefits of COVID-19 prevention to comply with prevention guidelines issued by the WHO and the Ministry of Health in Pakistan. When compared to recent studies, the cues to action for the study participants could have been influenced by misinformation regarding the causes and treatment of the SARS-CoV-2 virus, distrust in local government and media figures, misplaced assurance in the effectiveness of nonmedical treatments, and conspiracy narratives related to religious beliefs concerning a viral disease like COVID-19 [ 19 , 38 ]. A recent study in Macao, China, found that perceived susceptibility was the motivation for the participants to comply with prevention guidelines [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…To complicate the matter, global health inequities in affordability and the timing of COVID-19 vaccine sales to low-income countries (in comparison with high-income countries) still leaves preventive measures such as social distancing and face coverings as the only means to control the spread of SARS-CoV-2 [ 18 ]. A lack of trust in scientific facts, in favor of here-say and conspiracy theories, can be challenging to science-based interventions concerning COVID-19 [ 19 ]. A distrust in science may lead to an inability to learn or believe even the simplest facts about COVID-19.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Also, the study findings highlighted that the HCPs generally demonstrated good knowledge and prevention behaviors of COVID-19, which is in line with a study conducted by Yanti et al (2020), which suggests that 99% of Indonesian citizens had had good knowledge and behaviors of the COVID-19 prevention programs. Health care providers' knowledge is crucial in the pandemics period, including the current situation of the COVID-19 outbreak (Asemahagn, 2020;Qian et al, 2020;Viswanathan et al, 2020), in which the HCPs' high level of knowledge significantly influences the number of cases and the prevention of COVID-19 (Haque et al, 2021;Shen et al, 2021). The proper prevention behaviors among HCPs might be achieved through the experiences, particularly during the battle against the COVID-19 pandemic.…”
Section: Discussionmentioning
confidence: 99%